2003
DOI: 10.1007/s00213-003-1490-2
|View full text |Cite
|
Sign up to set email alerts
|

A microdialysis profile of ?-endorphin and catecholamines in the rat nucleus accumbens following alcohol administration

Abstract: The alcohol-induced release of beta-EP and dopamine in the NACB is dose-dependent, where the highest dose resulted in more pronounced concentrations in the dialysate. Furthermore, the increase in the extracellular levels of dopamine appeared to occur at an earlier time point following alcohol administration, than for beta-EP. These results suggest that alcohol stimulates dopamine and beta-EP in the NACB, but probably does so via independent mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
120
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(134 citation statements)
references
References 51 publications
13
120
0
1
Order By: Relevance
“…The sex-specific change in met-enkephalin levels may also explain why only ethanol-exposed female mice are less sensitive to the low-dose stimulant effect of ethanol [1]. Acute ethanol exposure increases the opioid peptide betaendorphin in NA [21,26]. Additionally, enkephalinase inhibitor, which potentiates the action of endogenous enkephalins, increases alcohol intake [8], while an opioid antagonist administered into the NA decreases the animal's response to alcohol [12].…”
Section: Discussionmentioning
confidence: 99%
“…The sex-specific change in met-enkephalin levels may also explain why only ethanol-exposed female mice are less sensitive to the low-dose stimulant effect of ethanol [1]. Acute ethanol exposure increases the opioid peptide betaendorphin in NA [21,26]. Additionally, enkephalinase inhibitor, which potentiates the action of endogenous enkephalins, increases alcohol intake [8], while an opioid antagonist administered into the NA decreases the animal's response to alcohol [12].…”
Section: Discussionmentioning
confidence: 99%
“…To our understanding, however, the most convincing proposal to comprehend the neural mechanism by which these receptors participate in ethanol sensitization may be related to the actions of the mu opioid receptor endogenous ligand, b-endorphin. Ethanol administration produces an increase in b-endorphin release, as measured by in vivo microdialysis in the NAcb (Olive et al, 2001;Marinelli et al, 2003). Also, acute administration of ethanol increased b-endorphin neurotransmission in the ventral tegmental area (VTA) (Rasmussen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…These include alterations in the function of the cholinergic, dopaminergic, g-aminobutyric acid, glutamatergic, opioidergic, and serotonergic neurotransmitter systems (for review see Eckardt et al, 1998). In the case of the endogenous opioid system and its receptor subtypes (m, d, kFselective for the three main classes of endogenous opioids: b-endorphin, enkephalins, and dynorphins, respectively), acute ethanol has been shown to stimulate the release of b-endorphin, enkephalins, and dynorphin in humans and rats (Gianoulakis et al, 1996;Marinelli et al, 2003Marinelli et al, , 2004Dai et al, 2005;Marinelli et al, 2005Marinelli et al, , 2006. Blockade of the receptors for these endogenous ligands by naltrexone and naloxone has been shown to reliably decrease ethanol consummatory behaviors (Gonzales and Weiss, 1998;Stromberg et al, 2001;Coonfield et al, 2002;Shoemaker et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nalmefene is also classified as a general opioid receptor antagonist and is equipotent with naltrexone at the m-opioid receptor, but unlike naltrexone, has a higher affinity for the k and d receptors in rats (Michel et al, 1985) and the k receptor in humans (Bart et al, 2005). Therefore, even at low doses, nalmefene can be considered a 'true' general opioid receptor antagonist.Thus, based on the fact that naltrexone and nalmefene have dissociable binding profiles at the opioid receptors, and that previous research has shown acute changes in bendorphin, met-enkephalin, and dynorphin in response to ethanol (Gianoulakis et al, 1996;Marinelli et al, 2003Marinelli et al, , 2004Marinelli et al, , 2005Marinelli et al, , 2006Dai et al, 2005), the purpose of the present study was to compare ligands with mechanisms of action that are either m-opioid (ie naltrexone) or m-, d-, and k-opioid (ie nalmefene) receptor based for their ability to attenuate ethanol self-administration in nondependent and ethanoldependent rats during acute withdrawal. Furthermore, to test directly the contribution of dynorphin systems to the increased ethanol self-administration observed during acute withdrawal, central k-opioid receptors were selectively targeted for antagonism in nondependent and ethanoldependent rats.…”
mentioning
confidence: 99%